Moderate Da’wa Strategy of Islamic Boarding School in Multicultural Society and Muslim Minority - Zilfa, Rohil; Huriyah, Lilik (Da’wa and Communication Faculty of the Sunan Ampel State Islamic University, Surabaya, Indonesia., 2020)
This study focuses on the strategy of da’wa moderate from the religious figure, Islamic education institution, and Islamic boarding school (pesantren) that shows the peaceful face, tolerant, democratic that was accepted with the multicultural society and Muslim minority. The location of this research is Pesantren Manba’ul ‘Ulum in the Loloan Timur, Jembrana, Bali province it survived in the multicultural society. This study uses a qualitative approach. Informants were selected using purposive sampling and snowball sampling techniques. Meanwhile, data collection used interviews, documentation, and observation. Data analysis uses a three-oath analysis consisting of data reduction, data presentation, and conclusion. Validity is based on credibility by using triangulation techniques on methods, sources, and theories. This study found the strategi of da’wa moderate Pesantren Manba’ul ‘Ulum in the multicultural society and Muslim minority are (1) continuing the culture “Ngeruwah”, (2) implanting the values of tolerance on learning processes for the student of pesantren and society, (3) accommodating majority groups (Hindu) in a non-religious agenda, such as education, sport, and other agenda.